Monoclonal antibody (UCHL1) that recognises normal and neoplastic T cells in routinely fixed tissues. - Norton, A; Ramsay, A; Smith, S; Beverley, P; Isaacson, P (1986)
UCHL1 is a murine monoclonal antibody that recognises a 180-185 kD determinant on CD4 (72%) and CD8 (36%) positive T cells. This antibody is effective in formalin fixed and paraffin embedded tissues, using the immunoperoxidase method. One hundred and forty three cases of malignant lymphoma were examined. Neoplastic cells in 100% of cases of Mycosis fungoides (n = 10), 83% of cases of peripheral T cell lymphoma (n = 25), and 78% of cases of (T-ALL) T acute lymphoblastic lymphoma (n = 9) were stained by this antibody. In addition, staining was seen in 100% of cases of malignant histiocytosis of the intestine (n = 13), a condition now thought to be a T cell lymphoma. Two cases of true histiocytic lymphoma were also positive. This antibody stained neither the neoplastic cells in a wide range of B cell lymphomas (n = 62) nor Reed-Sternberg cells in 16 cases of Hodgkin's disease. UCHL1 also stained neoplastic cells in four cases of granulocytic sarcoma. A panel of normal tissues was similarly studied. Staining was seen in normal T cells and mucosal intraepithelial lymphocytes, macrophages, mature myeloid cells, and endometrial stromal granulocytes. UCHL1 is a monoclonal antibody that identifies T cells in formalin fixed paraffin embedded tissues, and should prove useful for diagnosing T cell lymphomas, especially when only formalin fixed tissue is available for diagnosis.